SAFETY OF OPHTHALMIC BIOLOGICS: A SYSTEMATIC REVIEW - Ana Penedones; Diogo Mendes; Carlos Alves; Francisco Batel Marques (Formifarma, LDA., 2015)
Objectives: The present study evaluates the safety of ophthalmic biologics. Methods: The website of European Medicines Agency was searched in order to identify the biologics with approved therapeutic indications in ophthalmology. MEDLINE, Cochrane Library and ClinicalTrials.gov databases were searched systematically, up to October 2014. The study was divided in two settings: pre- and postmarketing. Phase III and phase IV randomized controlled trials and their extension and follow-up studies were included. Cochrane collaboration risk of bias evaluation tool was used to assess methodological quality. Adverse events were classified as ocular (related and non-related with injection procedure) and non-ocular (related and non-related with systemic inhibition of vascular endothelial growth factor). Incidences of all adverse events were estimated. Results: Three biologics with therapeutic indications approved in ophthalmology were identified: pegaptanib, ranibizumab and aflibercept. Twenty-two studies were included, of which 14 considered the pre-marketing setting and 8 refer to the post-marketing setting. The most frequent ocular and non-ocular adverse events were common to all biologics studied. Ocular adverse events related with injection procedure were rare (≤1%). The incidence of non-ocular adverse events related with systemic inhibition of VEGF was superior in post-marketing compared to pre-marketing setting (1,0%-1,3% vs. 0,7-1,1%). Conclusions: Ophthalmic biologics' safety profile was favorable. However, this study identified some adverse events, such as thromboembolic events, that deserve further research.